The effect of different ge concentration on the characteristics of strain silicon MOSFET - Jin, Wong Yah (2007)
Strained silicon is a layer of silicon in which the silicon atoms are stretched beyond their normal interatomic distance. This can be accomplished by putting the layer of silicon over a substrate of silicon germanium (SiGe).